Pengembangan Media Pembelajaran Berbasis PowerPoint Interaktif Materi Perubahan Wujud Zat untuk Siswa Kelas IV SD - Ermawati, Alia; Rista, Lutvi Fidya; Ummah, Alisya Roisatul; Putri, Faza Brilliani Wahono; Umah, Silvia Nashihatul; Istiq'faroh, Nurul; Zahroh, Ulfi Aminatuz (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2024)
The development of interactive PowerPoint-based learning media with material on changes in the state of matter is an innovation that can help students' understanding of learning in grade IV of elementary school. This study was conducted based on the problem of the lack of innovation in the learning media used, which has triggered a decline in student learning outcomes. The research method used is Research and Development (RnD). The subjects used in this study included 2 validators, namely media experts and material experts, and 8 questionnaire respondents, namely grade IV elementary school students. The results of the study showed that interactive PowerPoint-based learning media were very suitable for use in learning. The results of the study indicate that interactive PowerPoint-based learning media is very feasible to be used in learning. This result is shown from the average assessment of expert validation of 95.55% with a very good category.